Textbook outcomes in the laparoscopic common bile duct exploration of choledocholithiasis: a new comprehensive quality evaluation criterion - Teng, Da; Xu, Yue (Frontiers in Surgery, 2025)
BackgroundThe textbook outcome (TO) is an innovative composite criterion that encompasses multiple perioperative events. It serves as a measure of perioperative quality and provides an objective reflection of the most desirable outcome. The concept of TO has been introduced to laparoscopic common bile duct exploration (LCBDE) to establish TO criteria and identify key risk factors associated with TO failure.MethodsClinical data from 225 patients who underwent LCBDE for choledocholithiasis were retrospectively analyzed, categorizing them into “TO” and “TO-failure” groups based on whether TO was achieved. TO criteria were defined based on existing literature and the perioperative characteristics of LCBDE, including no residual stones, no bile leakage, no severe postoperative complications, no readmission or death within 30 days, and no extended hospitalization. The TO incidence rate was calculated, and univariate and multivariate logistic regression analyses were employed to identify perioperative characteristics and independent risk factors contributing to TO failure.ResultsA total of 167 patients (74.2%) achieved TO. Independent risk factors for TO failure included ASA score ≥ 3 (OR: 9.260, 95% CI: 2.292–37.418, P = 0.002), T-tube drainage (TTD) (OR: 5.332, 95% CI: 1.625–17.497, P = 0.006), preoperative combined cholecystitis (OR: 3.448, 95% CI: 1.091–10.897, P = 0.035), preoperative combined cholangitis (OR: 11.468, 95% CI: 2.841–46.284, P = 0.001), and operative time ≥ 90 min (OR: 3.066, 95% CI: 1.253–7.503, P = 0.014).ConclusionsApplying the TO concept to LCBDE facilitates a more comprehensive and objective evaluation of perioperative characteristics in patients with choledocholithiasis. This approach contributes to the standardization of quality assessment in LCBDE, promoting the continuous improvement of surgical quality. Furthermore, achieving TO can enhance the overall quality of the healthcare system, potentially reducing healthcare costs. Additionally, TO aligns more closely with patient preferences, representing the optimal surgical outcome. As a holistic assessment tool, TO is poised to become a definitive quality standard for evaluating surgical procedures.